Comparison of thermodilution and indirect Fick cardiac outputs in pulmonary hypertension. (1st May 2018) - Alkhodair, Abdullah; Tsang, Michael Y.C.; Cairns, John A.; Swiston, John R.; Levy, Robert D.; Lee, Lisa; Huckell, Victor F.; Brunner, Nathan W.
Abstract: Background: The accurate measurement of cardiac output (CO) is required in patients with pulmonary hypertension (PH).While both the thermodilution (TDCO) and indirect Fick (IFCO) methods are commonly used, there is little data comparing them in patients with PH. Methods: We performed a retrospective analysis of patients evaluated at our center. All patients who had right heart catheterization (RHC) within 3 months of an echocardiogram, and CO assessment by both TDCO and IFCO methods were included. Bland-Altman analysis was used to assess agreement between the two methods. We further evaluated their agreement in each sex, and within tertiles of age, BMI and TR severity. We investigated the correlation between each method of CO and objective parameters of right ventricular function on echocardiography. Results: In a cohort of 168 patients, the correlation between IFCO and TDCO was modest at (r = 0.61). On average, values for CO were lower with IFCO than with TDCO, by 0.62 L/min (95% CI −0.82, −0.40). This difference was greater for females: 0.86 L/min (95% CI −1.08, −0.63) and in the highest tertile of BMI: 0.97 L/min (95% CI −1.4, −0.55). Moderate and severe TR did not in general result in lower TDCO values. Echocardiographic parameters of right ventricular function were correlated more strongly with TDCO than with IFCO. Conclusion: In PH patients, IFCO was substantially lower than TDCO on average, suggesting that these two techniques cannot be used interchangeably. TDCO correlated more strongly with echocardiographic measures of RV function, suggesting that it may be preferred over IFCO. Highlights: Standardization of cardiac output measurement is important. We found the indirect Fick method gave lower cardiac outputs than thermodilution. Thermodilution correlated more strongly with echo measures of RV function.